Alkyl and Aryl 4,5-Dichloro-6-oxopyridazin-1(6H)-carboxylates: A Practical Alternative to Chloroformates for the Synthesis of Symmetric and Asymmetric Carbonates - Moon, Hyun Kyung; Sung, Gi Hyeon; Yoon, Yong-Jin; Yoon, Hyo Jae (Synlett, 2016)
Symmetric and asymmetric carbonates were synthesized by using alkyl or aryl 4,5-dichloro-6-oxopyridazin-1(6H)-carboxylates. Five aryl 4,5-dichloro-6-oxopyridazin-1(6H)-carboxylates were converted into the corresponding diaryl carbonates in good to excellent yields by treatment with potassium carbonate in refluxing THF. When the 4,5-dichloro-6-oxopyridazin-1(6H)-carboxylates were treated with aliphatic or aromatic alcohols in the presence of potassium tert-butoxide in toluene at room temperature, they gave the corresponding symmetric or asymmetric carbonates in moderate to excellent yields. Alkyl and aryl 4,5-dichloro-6-oxopyridazin-1(6H)-carboxylates are therefore efficient, stable, and ecofriendly alternatives to chloroformates.
Keywords: pyridazines; alcohols; phenols; carbonates; alkoxycarbonylations; acyl-transfer agents